Myotoxin-neutralizing peptides - Lohse, Brian (2018)
The present invention relates to polypeptides having myotoxin-neutralizing properties and their use for treatment of envenomation. The present invention further relates to methods for neutralizing a venom using the polypeptide of the invention as well as to methods of treatment of envenomation by administering said polypeptide to a subject in need thereof.